Influence of air changes per hours (ACH) on human thermal comfort under stratum ventilation setting in a single isolated wardroom - Siti Najiah, Rosminahar; Mohamad Nur Hidayat, Mat; Muhammad Faiz Hilmi, Rani; Yinn, Wong Keng; Akrami, Mohammad (Semarak Ilmu Publishing, 2025)
Proper ventilation is critical in hospital environments to ensure optimal conditions for healthcare professionals and patients. However, achieving a balance between contaminant removal and thermal comfort remains a challenge, particularly in enclosed spaces like wardrooms. This study investigates the relationship between air changes per hour (ACH) and human thermal comfort, specifically through the lens of the Predicted Mean Vote (PMV) metric in stratum ventilation settings. By utilizing Computational FluidDynamics (CFD) simulations, we explore various ACH scenarios to evaluate their effects on PMV. Our findings reveal that increased ACH rates often correlate with heightened discomfort among patients, highlighting the complex balance required in the ventilationdesign. In stratum ventilation systems, distinct PMV values emerge because of differingairflow dynamics, demonstrating that while some areas may meet comfort standards, discomfort persists elsewhere. This research emphasizes the significant impact ofACH on thermal comfort in healthcare settings, advocating for nuanced ventilation strategies that consider both contaminant removal efficiency and occupant comfort. The insights gained contribute to a deeper understanding of ventilation design in healthcare facilities, where a conducive indoor environment is vital for the well-being of both patients and staff.